A Model to Compute the Solar Parameters in Relation to Determining the Optimal Angles for Solar Panels in Many Locations in Iraq - Roomi, Thaer O.; Nemah, Hussain A.; Shubbar, Ramiz M. (Iraqi Journal of Science, 2021)
Directing solar panels in a way that collects the largest possible amount of solar energy is still attracting a lot of attention due to the continuous need to get clean, inexpensive renewable energy. Iraq is one of the countries characterized by the abundance of solar energy but the investment in this field has been far below ambition. In this study, an application developed with the visual basic programing language was used to compute precisely various solar angles and parameters , as a powerful tool for engineers and researchers. The outputs of the model were tested and discussed in detail. The air mass values were also computed for three cities: Mosul, Baghdad, and Basra. The results showed that the best time to acquire the solar radiation would be from 10 am to 2 pm (local time), the period that has the lowest values of air mass. Additional useful calculations that can be estimated by the application were the terrestrial irradiances from four empirical models for the clear sky: Roledo-Soler, Adnot, Kasten – Czeplak, and Berger-Duffie. The calculated values of terrestrial irradiance were compared with observed data measured by automatic weather station. The application simulated the actual values with some deviations due to the existence of clouds and aerosols. Kasten – Czeplak model was recommended to be used in Iraq since it was the best model to simulate the measured values. The comparison between the model’s output and the measured values on a daily basis on the 21st of June showed good agreement. The study suggested that the solar panels should face the south direction with a change of the tilt angle of the panels from 25o in June to a value of 60o each month towards the coldest months by an increment of 5 degrees.